Studi Farmakovigilans Penggunaan Obat Antiretriviral di Puskesmas Semarang - Lestari, Asih Puji; Meki Pranata (Jurnal Farmasi UIN Alauddin Makassar, 2023)
The increase in cases of the HIV epidemic in Indonesia at the end of 2009 continued to increase, it is estimated that around 332.200 people are living with HIV. This figure has almost doubled from 2005 as many as 170.000 people living with HIV. Provision of extensive anti-retroviral therapy (ART) also result in mutations of the HIV virus that can lead to resistance. The purpose of this study was to determine the description and incidence of unwanted drug reactions in patients who were prescribed antiretroviral drugs and to assess the quality of life of patients who had received anti-retroviral drug prescriptions at the public health center. This type of research is a descriptive observational study, data collection was carried out retrospectively on patients who received herbal medicine at the public health center. The sampling technique in this study was quota sampling with a research instrument in the form of ROTD interview sheets taken from the Naranjo algorithm. The results showed that the use of antiretroviral drugs (ARVs) would cause unwanted drug reactions such as nausea, vomiting, dizziness (vertigo) which were categorized as possibilities and possibilities.